The geopolitics of South Asia : from early empires to the nuclear age - Chapman, Graham (Ashgate, 2009)
Anyone who is planning on carrying out research in South Asia, or indeed, simply wishes to understand a little about this cultural heartland should read this enthralling book. By studying the main forces which brought about historic, linguistic and economic development, Professor Chapman contends that the lynch-pin of this sub-continent's story is a geo-political one. In addition to the material on the Northwest frontier, Afghanistan and Kashmir which was added for the second edition, the Northeastern borderlands are also now examined in this fully revised third edition. The current geopolitica.